EFFECT OF PLANT GROWTH REGULATORS AND PHYSICAL FACTORS ON IN VITRO HIGH FREQUENCY REGENERATION OF GRASS PEA - S. Barpete; S. F. Özcan.; K. M. Khawar; S. Özcan (Journal of Animal and Plant Sciences, 2016)
Grass pea (Lathyrus sativus L.) is highly nutritious and protein rich legume crop; however, presence of ODAP (β-N-Oxalyl-L-α, β-diaminopropionic acid) has restricted its use for human and animal consumption. There is need for accelerated breeding of low or zero ODAP cultivars to ensure safer and wider use of grass pea through conventional and biotechnological approaches. The study investigated   solidified  MS medium containing a combination  of  thidiazuron (TDZ) and α-naphthalene acetic acid (NAA) concentrations for improved regeneration of grass pea using stem with two nodes (binodal) explant under photosynthetic photon flux density (PPFD) of 20 µmol m-2 s-1 light intensity. The results showed that combination of low light intensity, phytagel as gelling agent and TDZ - NAA was very effective for high frequency shoot regeneration after 3 weeks culture. Maximum number of 37.6 shoots per explants was noted on MS medium containing 0.75 mg/L TDZ - 0.25 mg/L NAA, with 96.66% shoot induction. Healthy, well growing shoots were rooted on ½ × MS medium (micro, macro elements and vitamins) containing 0.25 mg/L Indole-3-butyric acid (IBA) that resulted in 83.60% rhizogenesis. Peat moss potted plants induced hundred percent acclimatization and survival. Compared to other rooting substrates, peat moss acclimatized plants were more vigorous, flowered and set seeds under glass house conditions. High regeneration and acclimatization percentage signifies importance of this work for biotechnological based grass pea breeding.
Keywords: Binodal stem; grass pea; in vitro; Lathyrus sativus L.; Light intensity; Phytagel